PENERAPAN TELEWORK HUBS PADA LEMBAGA PERGURUAN TINGGI TERBUKA JARAK JAUH: PELUANG DAN TANTANGAN - Indra Pratama Putra Salmon; Ridho Harta; Ardik Ardianto; Amud Sunarya (REFORMASI, 2023)
Utilization of tools and adoption of technology-based work systems (ICT) in the midst of the wide reach of remote tertiary institutions (PTJJ) and the high number of resources is still not optimal. This research uses qualitative methods with a phenomenon-based approach. Narrative reviews of literature studies are the main approach in writing reviews by applying systematic, empirical, and evidence-based protocols. The data and information included is credible, transparent and accountable as a source of research. The object of study is the flexible working space practice at the Ministry of Finance which is then placed in the framework of the PTJJ institution, namely the Open University. The results of the study show that optimizing the use of tools and adopting technology-based work systems (ICT) through the telework hubs framework has the opportunity to drive several performance variables for PTJJ institutions such as work ability, motivation, working conditions and cooperation/collaboration. Some of these variables are important variables in the framework of educational industry competition and the dynamics of challenges in resource management at PTJJ institutions, both managing resources or managed resources. The novelty of this study is research on work flexibility schemes which have not been widely studied, especially in PTJJ institutions in Indonesia. The main implications of the research are preparation recommendations in the context of optimizing the use of tools and the adoption of technology-based work systems (ICT) in PTJJ.AbstrakPemanfaatan tools dan pengadopsian sistem kerja berbasis teknologi (ICT) di tengah luasnya jangkauan lembaga perguruan tinggi jarak jauh (PTJJ) dan tingginya jumlah sumber daya masih belum optimal. Penelitian menggunakan metode kualitatif dengan pendekatan berbasis fenomena. Tinjauan naratif dari studi literatur menjadi pendekatan utama dalam penulisan kajian dengan menerapkan protokol sistematis, empirik, dan berbasis bukti. Data dan informasi yang dicantumkan merupakan data-data kredibel, transparan, dan mampu dipertanggungjawabkan sebagai sumber kajian. Objek kajian berupa praktik flexible working space di Kementerian Keuangan yang kemudian diletakkan pada kerangka kerja lembaga PTJJ yakni Universitas Terbuka. Hasil kajian menunjukkan bahwa optimasi pemanfaatan tools dan adopsi system kerja berbasis teknologi (ICT) melalui kerangka telework hubs berpeluang mendorong beberapa variabel kinerja lembaga PTJJ seperti kemampuan kerja, motivasi, kondisi kerja dan kerjasama/kolaborasi. Beberapa variabel tersebut merupakan variabel penting dalam rangka kompetisi industri pendidikan dan dinamika tantangan pengelolaan sumber daya pada lembaga PTJJ, baik sumber daya pengelola atau sumber daya yang dikelola. Kebaruan kajian ini adalah penelitian tentang skema fleksibilitas kerja yang masih belum banyak diteliti khususnya pada lembaga PTJJ di Indonesia. Implikasi utama penelitian yakni rekomendasi persiapan pada konteks optimasi pemanfaatan tools dan pengadopsian sistem kerja berbasis teknologi (ICT) di PTJJ.